Parallel Miocene‐dominated diversification of the lichen‐forming fungal genus Oropogon (Ascomycota: Parmeliaceae) in different continents. Issue 6 (13th November 2017) - Wei, Xin-Li; Leavitt, Steven D.; Huang, Jen-Pan; Esslinger, Theodore L.; Wang, Li-Song; Moncada, Bibiana; Lücking, Robert; Divakar, Pradeep K.; Lumbsch, H. Thorsten
Abstract: Lineages with broad, intercontinental distributions can provide insight into factors that influence diversity across both temporal and geographic scales. Lichens are well known for distinct biogeographic distribution patterns, including a high number of lineages with intercontinental distributions. The lichen‐forming fungal genus Oropogon, from one of the largest families of lichen‐forming ascomycetes, Parmeliaceae, occurs in both Asia and the Neotropics. How this genus obtained this disjunct distribution is not currently known. To better understand factors shaping diversity in Oropogon, we (i) estimated the timing of diversification of major clades within this genus; (ii) inferred the historical biogeography of Oropogon ; and (iii) identified factors that potentially affected the distribution and evolution of this genus. Our results suggest that the genus originally radiated during the early Miocene, with subsequent diversification events occurring during the middle Miocene. Ancestral area reconstructions for Oropogon suggest that the genus was either widespread with subsequent separate diversification in Asia and America or originated in the New World (America), with subsequent migration to Asia. We hypothesize that the Mi‐1 glaciation impacted diversification of Oropogon species in Asia, and that the rise of major mountain ranges, such as the Himalayas, helped promote diversification in Oropogon in the Old World.